CREATING NATIONAL GERMANY: HISTORY, POLITICS AND LAW (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
The historical state-legal development of Germany in many ways is specific, because although the German state was created after the Franco-Prussian war of 1871, certain announcements and elements of its statehood existed even before its official creation. With the Paris Peace Aagreement of May 30, 1814, German states were declared autonomous and joined forces in a federal alliance. The decisions of the Vienna Congress of 1815 were regarded as the fundamental law of the German Union, and its regulation was envisaged by the German federal acts, which in a small part were altered by the Viennese federal acts of 1820. In the second half of the 19th century the conditions for the national formation of Germany matured, and this was largely the merit of the Prussian chancellor Otto von Bismarck. His goal was to unite Germany around Prussia and for that purpose he used manipulation, diplomacy and power. At the end of the 19th century and at the beginning of the 20th century, the strengthened German state and the increased industrial capital it possessed conditioned the demand for "its place under the sun" in the imperialist world politics, which surpassed its state borders. At a time when the colonial policies of the great and powerful states largely captured the springs and centers of imperial holdings in Africa and Asia, the belated birth of this gigantic state has problematized the balance of powers in Europe. The imperialist German project failed in 1918. For these reasons, this paper deals with the legal and political aspects of national Germany, from its creation to the Second World War.